Roads hazards of road construction on birds and cost evaluation in Central Kazakhstan - Nargiza Askarova (Theoretical Hypotheses and Empirical Results, 2024)
The research addresses the necessity of exploring road hazards occurring during motorway construction on birds in Central Kazakhstan. The study contains materials about bird’s species, including rare ones, obtained through conducting area observations. It further identifies main hazards and evaluates assessment on birds, their nests. Moreover, the research highlights critical points in the region, proposes mitigation measures. With the help of similar research and projects, the study tries to make an approximate evaluation of the cost of proposed measures.